4′-Alkylseleno-4-cyanobiphenyls, nSeCB: synthesis and substituent effects on the phase-transition and liquid crystalline behaviors. Issue 43 (14th October 2022) - Arakawa, Yuki; Shiba, Takuma; Igawa, Kazunobu; Sasaki, Shunsuke; Tsuji, Hideto
Abstract : A homologous series of 4′-alkylseleno-4-cyanobiphenyls ( n SeCB) was synthesized and their phase-transition behaviors were investigated and compared with those of the alkyl, alkoxy, and alkylthio homologs. Abstract : The synthesis and phase-transition behavior of a novel homologous series of 4′-alkylseleno-4-cyanobiphenyls [ n SeCB, where n represents the number of carbon atoms in the alkyl chains ( n = 1–8)] is reported. Polarized optical microscopy and differential scanning calorimetry revealed that the n SeCB homologs with n = 1–6 exhibited monotropic nematic (N) phases at low temperatures, which appeared below 10 °C for n SeCB with n = 3–6. However, no liquid crystal (LC) phase was observed in the n SeCB with n = 7 and 8. In addition, we compared the phase-transition behaviors of the n SeCB homologs with those of the alkyl-, alkoxy-, and alkylthio-based homologous series ( n CB, n OCB, and n SCB, respectively). The LC phases of certain n CB and n OCB were enantiotropic, whereas those of all n SCB and n SeCB were monotropic. The longer-chain n CB, n OCB, and n SCB homologs formed layered smectic A (SmA) phases, whereas only N phases were observed for the n SeCB homologs within the tested range of the chain lengths. The n SeCB series showed the lowest isotropic-to-N phase-transition ( T IN ) temperatures for all chain lengths except 1SeCB. The low mesogenic ability and LC phase-transition temperatures of n SeCB were attributed to the higher flexibility, steric bulk, and lower molecular anisotropy due to the C–Se–C bond, which has lower rotational barriers, longer bond lengths, and smaller bond angles than the other bonds compared herein. The varying alkyl-chain lengths had a greater influence on the phase-transition temperatures of the n SeCB homologs than those of the other homologs. Furthermore, the single-crystal structural analysis of 1SeCB was conducted to obtain insights into the phase-transition behaviors.